Critical Leadership in Reconciliation for Church-Based Conflict in Halmahera, Indonesia: Relevansi Kepemimpinan Kritis dalam Konflik Gereja Halmahera - Tjaja, Broery Doro Pater; Lattu, Izak Y. M.; Therik, Wilson M A. (IAIN Ambon, 2024)
This article attempts to look at church-based conflicts using the Critical Leadership (CL) approach in collaboration with Actor Network Theory (ANT) and finds its relevance for communal life. Using an interdisciplinary approach with qualitative methods, the collaboration of CL and ANT found that all resources of religious organizations in conflict situations are networks of actors whose interactions legitimize power and can also be a path to reconciliation. From the lens of CL and ANT, conflicts that result in dualism in church organizations are seen as both a process and a result of actor interactions and relations during the conflict. Therefore, reconciliation can also be used as a process and a result of the CL and ANT mechanisms which then present policy recommendations such as the intensity of structural actor meetings that can produce joint programs for church members, and can also be a path for institutional unification and reconciliation.